O AGRICULTURĂ DIFERITĂ ESTE POSIBILĂ, DAR ȘI NECESARĂ. GRUPURILE DE PRODUCĂTORI ÎN CONTEXTUL DEZVOLTĂRII DURABILE ȘI REZILIENȚEI ZONEI MONTANE PRIVIND CRIZELE ACTUALE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
A Different Kind of Farming is Possible and Necessary. Producer Groups in the Context of Sustainable Development and Resilience of the Mountain Area to Current Crises.Due to the considerably limited possibilities of agricultural land use, because of climatic conditions, slopes and geological substratum, the mountain area is considered disadvantaged. This area is ecologically fragile, entailing great efforts, restrictions in the pursuit of certain economic activities and land use, and increasing the costs of all activities and works. All these aspects give agricultural producers a right to a difference and compensation. Mountain areas must therefore benefit from a specific policy, defined according to the principles of sustainable development, which ensures the needs of the present without compromising the chances of future generations. The resilience of upland areas refers to their capacity to adapt to and withstand changes and impacts in their environment. Aspects that contribute to the resilience of mountain areas are related to biodiversity, resilient infrastructure, management of natural and human resources, education, innovation, organisation and technology. The crises facing agriculture today – the energy crisis, the food insecurity crisis, the harsh realities and their impact are strongly felt everywhere and affect not only local, regional agriculture and food systems, but create new challenges for almost all sectors of life. Agricultural policies focus on knowledge development and innovation through the expansion of the farm advisory system, training and business development, green payments, increased support for knowledge transfer and innovation, the European Innovation Partnership on agricultural productivity and sustainability.